FORMULASI DAN EVALUASI PEMBUATAN PRODUK NUTRASETIKAL SIRUP DARI EKSTRAK BUAH JERUK KUKU HARIMAU (Citrus medica L.) SERTA UJI AKTIVITAS ANTIOKSIDANNYA DENGAN MENGGUNAKAN METODE DPPH (2,2-DIFENIL-1-PIKRILHIDRAZIL) - Gultom, Roby; Gulo, Septi Kristina; Siagian, Hartika Samgryce (Universitas Imelda Medan, 2023)
Syrup nutraceutical product has been made from the fresh extract of Tiger Nails fruit (Citrus Medica L). This research is a laboratory experimental. Fresh extracts were divided into FI (10%), FII (20%) and FIII (40%). The formulations were compounds of extracts, sugars and waters. Organoleptic’s test results were color is yellow, orange’s aroma, sweet taste and thick textures. Hedonic’s test showed the color of Formulations were not like by panelists (60%) and aroma test of FII showed panelists like it (60%). The texture test of formulations showed the panelists like it (70%) and the taste test of FI showed the panelists were very like it (70%). The pH values were ranged from 4-5. The fastest dissolving time test showed from FI (8 seconds). The highest viscosity test was showed by FII (6,08 poise). The determination of vitamin C levels using UV-Vis Spectrophotometry showed FIII the highest levels of vitamin C (0.828%). But all antioxidants activity had low activity. FIII has the highest IC50 value (454172,74 ppm). Anova test value showed 0,1505>0.05 that means the antioxidant activity were not significantly different. Tukey test showed the comparison of antioxidant properties between the formulations groups showed a significance value of 0,135 > 0.05.